Socialization of Waste Sorting and Training on Making Liquid Organic Fertilizer from Household Organic Waste in Wedoroklurak Village, Candi Sidoarjo: Sosialisasi Pemilahan Sampah Dan Pelatihan Pembuatan Pupuk Organik Cair dari Sampah Organik Rumah Tangga di Desa Wedoroklurak Candi Sidoarjo - Syahrorini, Syamsududhha; Istikomah; Anggreini, Antika Dhuwi; Khoirunnisak; Tresnawati5, Sri Nanda; Syeny, Syndy (Procedia of Social Sciences and Humanities, 2022)
Garbage problem is a common thing in every area. Both the problem of disposal, management, and recycling of these materials. In Wedoroklurak Village the problem of organic waste is still quite available every day after household waste only because it is collected at the TPS and there has been no attempt to utilize it. This problem needs to be considered because high piles of garbage can cause unpleasant odors and are a source of disease. In addition, if it is burned, soil contamination due to burning makes the land not become a suburb. This community service work program from Umsida has a vision to increase the awareness of the people of Wedoroklurak Village regarding the importance of managing household waste into something useful and dangerous for the environment if there is no proper handling. The mission to raise awareness is carried out by utilizing household waste such as vegetables, fruits, and food scraps into liquid organic fertilizer that can be used to fertilize soil and plants. This program was carried out on February 9 – March 10, 2022 which is part of the environmental program of the Umsida 2022 community service team. This program produces fertilizer from household waste by utilizing agricultural EM4 bioactivator which helps speed up the fermentation process. In addition, other materials used such as dry leaves and rice washing water are also important points in making POC from household waste. The method used is experimental, in which organic household waste such as stale rice, fruit, vegetables, and egg shells are collected and then chopped. Furthermore, rice washing water and activator (EM-4) with a volume of 300 ml and drying brown sugar were added, then allowed to stand for 3 to 4 weeks in an aerobic way.